Therapeutic efficacy of pyronaridine-artesunate (Pyramax®) against uncomplicated Plasmodium falciparum infection at Hamusit Health Centre, Northwest Ethiopia - Mihreteab Alebachew; Woyneshet Gelaye; Megbaru Alemu Abate; Heven Sime; Henok Hailgiorgis; Bokretsion Gidey; Mebrahtom Haile; Gudissa Assefa; Worku Bekele; Habtamu Belay; Jonathan B. Parr; Geremew Tasew; et al. (Malaria Journal, 2023)
Abstract Background Early case detection and prompt treatment are important malaria control and elimination strategies. However, the emergence and rapid spread of drug-resistant strains present a major challenge. This study reports the first therapeutic efficacy profile of pyronaridine-artesunate against uncomplicated Plasmodium falciparum in Northwest Ethiopia. Methods This single-arm prospective study with 42-day follow-up period was conducted from March to May 2021 at Hamusit Health Centre using the World Health Organization (WHO) therapeutic efficacy study protocol. A total of 90 adults ages 18 and older with uncomplicated falciparum malaria consented and were enrolled in the study. A standard single-dose regimen of pyronaridine-artesunate was administered daily for 3 days, and clinical and parasitological outcomes were assessed over 42 days of follow-up. Thick and thin blood films were prepared from capillary blood and examined using light microscopy. Haemoglobin was measured and dried blood spots were collected on day 0 and on the day of failure. Results Out of 90 patients, 86/90 (95.6%) completed the 42-day follow-up study period. The overall PCR-corrected cure rate (adequate clinical and parasitological response) was very high at 86/87 (98.9%) (95% CI: 92.2–99.8%) with no serious adverse events. The parasite clearance rate was high with fast resolution of clinical symptoms; 86/90 (95.6%) and 100% of the study participants cleared parasitaemia and fever on day 3, respectively. Conclusion Pyronaridine-artesunate was highly efficacious and safe against uncomplicated P. falciparum in this study population.